Xanthine oxidase mediates chronic stress-induced cerebrovascular dysfunction and cognitive impairment. Issue 6 (June 2023) - Burrage, Emily N; Coblentz, Tyler; Prabhu, Saina S; Childers, Ryan; Bryner, Randy W; Lewis, Sarah E; DeVallance, Evan; Kelley, Eric E; Chantler, Paul D
Xanthine oxidase (XO) mediates vascular function. Chronic stress impairs cerebrovascular function and increases the risk of stroke and cognitive decline. Our study determined the role of XO on stress-induced cerebrovascular dysfunction and cognitive decline. We measured middle cerebral artery (MCA) function, free radical formation, and working memory in 6-month-old C57BL/6 mice who underwent 8 weeks of control conditions or unpredictable chronic mild stress (UCMS) with or without febuxostat (50 mg/L), a XO inhibitor. UCMS mice had an impaired MCA dilation to acetylcholine vs. controls (p < 0.0001), and increased total free radical formation, XOR protein levels, and hydrogen peroxide production in the liver compared to controls. UCMS increased hydrogen peroxide production in the brain and cerebrovasculature compared to controls. Working memory, using the y-maze test, was impaired (p < 0.05) in UCMS mice compared to control mice. However, blocking XO using febuxostat prevented the UCMS-induced impaired MCA response, while free radical production and hydrogen peroxide levels were similar to controls in the liver and brain of UCMS mice treated with febuxostat. Further, UCMS + Feb mice did not have a significant reduction in working memory. These data suggest that the cerebrovascular dysfunction associated with chronic stress may be driven by XO, which leads to a reduction in working memory.